THE CHINESE VECTOR IN TAJIKISTAN’S FOREIGN POLICY - DODIKHUDOEV, Khurshed; NIYATBEKOV, Vafo (CENTRAL ASIA AND THE CAUCASUS, 2009)
Independent Tajikistan is seeking diverse contacts with all interested states. Under Soviet power the Central Asian republics remained in the shadow of the rest of the country, the disintegration of which finally gave them a chance to develop relations with other countries. At first, the world community remained indifferent to their existence and limited itself to general declarations. The People’s Republic of China, however, became aware that the three new Central Asian states in its northwestern provinces radically changed the foreign policy context. On 4 January, 1992 Dushanbe made one of its first foreign policy moves by signing a joint Tajik-Chinese communique on the establishment of diplomatic relations between the two countries at the embassy level. The date itself is an eloquent sign of Beijing’s interest in the political processes that swept the post-Soviet expanse in the late 20th century. China was one of the first states to recognize the independence of all the Soviet republics, including Tajikistan. In 1993 Chairman of the Supreme Soviet of Tajikistan Emomali Rakhmonov paid his first official visit to China on an invitation from the Chinese leaders. He traveled to Nanjing, Shanghai, and Urumqi and met top Chinese officials: Chairman of the PRC Jiang Zemin and Chairman of the Standing Committee of the National People’s Congress of China Yang Shangkun. The talks proceeded in a friendly and businesslike atmosphere. The sides discussed issues of mutual interest; Point 12 of the joint declaration said that relations between China and Tajikistan had good prospects. The visit produced another important decision on developing trade and economic relations on a priority basis. The sides pointed out their common position on the key issues. The visit demonstrated that China supported the young independent state; without this support Tajikistan could hardly attain many of its foreign policy goals in Asia. In 1996 the dialog between the two countries was given a new boost in the form of President Rakhmonov’s second visit to China. The sides identified the cooperation spheres of greatest mutual interest: agriculture, transport, the textile industry, the production of mineral fertilizers, etc. Since 1996 the dialog has been proceeding in the multisided format of the newly established Shanghai Forum. Before that Dushanbe and Beijing cooperated within the U.N. and CICA. The Chinese have identified the stages on the road from the Shanghai Forum to the SCO.